2021
DOI: 10.1111/aji.13405
|View full text |Cite
|
Sign up to set email alerts
|

Effect of injectable progestin‐only contraceptives, depot medroxyprogesterone acetate and norethisterone enanthate, on cytokine production during T‐cell activation

Abstract: Problem: There is paucity of human data about the effects of depot medroxyprogesterone (DMPA) and norethisterone enanthate (Net-En) use on systemic immune function, which may have implications for reproductive tract infection susceptibility and transmissibility. We sought to evaluate the impact of injectable contraceptive use on T-cell responsiveness using T cells exposed in vivo and tested ex vivo. Methods: Peripheral blood mononuclear cells were obtained from healthy, HIVnegative women after 30, 90 and 180 d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Research has examined the relationship between DMPA and Norethisterone enanthate use and the impact of immune cell responsiveness to identify whether using these POC may increase susceptibility to infections. However, in a study by Matubu et al 62 the exposure of CD4 + and CD8 + T cells to typical pharmacologic concentrations of DMPA was not found to cause immunosuppressive effects. Despite this, the depletion of cytokine-producing T cells may occur after prolonged DMPA use.…”
Section: Discussionmentioning
confidence: 86%
“…Research has examined the relationship between DMPA and Norethisterone enanthate use and the impact of immune cell responsiveness to identify whether using these POC may increase susceptibility to infections. However, in a study by Matubu et al 62 the exposure of CD4 + and CD8 + T cells to typical pharmacologic concentrations of DMPA was not found to cause immunosuppressive effects. Despite this, the depletion of cytokine-producing T cells may occur after prolonged DMPA use.…”
Section: Discussionmentioning
confidence: 86%
“…Although the dosedependency of this effect is clear, we cannot exclude that a transient reduction of the local immune defenses upon MPA administration in vivo, possibly involving cell apoptosis, is followed by inflammatory processes such as cell recruitment and activation, including CCR6-and CCR5-expressing HIV-1 target cells [45]. While attempting to mirror declining plasma levels of MPA upon injection, our model cannot recapitulate any potential long-term changes nor the impact of a prolonged use of MPA following multiple injections [46], owing to intrinsic limitations in tissue explant integrity/viability over time [21]. Multiple cell subsets and soluble factors likely contribute to the observed structural changes in the FGM of DMPA users, including stromal and epithelial cells and related growth factors [25,47].…”
Section: Discussionmentioning
confidence: 94%
“…Sex steroid hormones are inherently linked to the regulation of microbial populations in the FGT 42 . While endogenous oestrogen and its synthetic analogue estradiol have previously been associated with an increased abundance of beneficial Lactobacillus species, 43 the findings of previous studies on the effects of progestin‐only contraceptives, such as DMPA‐IM, on vaginal microbial communities have been inconsistent 22,44–50 . The injectable has also been linked to altered cell‐mediated immune responses, which in turn increase a woman's susceptibility to BV and STIs, including HIV.…”
Section: Discussionmentioning
confidence: 99%
“… 42 While endogenous oestrogen and its synthetic analogue estradiol have previously been associated with an increased abundance of beneficial Lactobacillus species, 43 the findings of previous studies on the effects of progestin‐only contraceptives, such as DMPA‐IM, on vaginal microbial communities have been inconsistent. 22 , 44 , 45 , 46 , 47 , 48 , 49 , 50 The injectable has also been linked to altered cell‐mediated immune responses, which in turn increase a woman's susceptibility to BV and STIs, including HIV. Recently, it has been demonstrated that effects of DMPA‐IM on genital inflammatory pathways may be modified by the FGT microbiome.…”
Section: Discussionmentioning
confidence: 99%